PEMBUATAN BIODIESEL DARI MINYAK GORENG MENGGUNAKAN KATALIS KOH DENGAN PENAMBAHAN EKSTRAK JAGUNG - Ndaru Okvitarini; Makrufah Hidayah I; Hantoro Satriadi; W Widayat (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Antioxidants on biodiesel can use for inhibit the oxidation events during storage or in use. The objective of this research are to study ratio corn ratio ethanol extract to oil and biodiesel and KOH consentration in biodiesel production Reactions were performed for three hours with a catalyst concentration process variables 0:25 to 1:25% and the ratio of cooking oil / corn ethanol extract of between 1:3 to 1:7. Then the separation of biodiesel from glycerol. Further test the properties of biodiesel density, viscosity, acid number, saponification number, peroxide value, iodine number. Results of analysis of 9 samples has characteristic that almost in accordance with SNI. It is proved that antioxidants work reduces the oxidation reaction. The highest conversion of biodiesel production is shown by the use reactants 1:7 is 91,75% and 1:25% catalyst is 91,5%.